Brazilian recommendations for the management of tuberculosis infection in immune-mediated inflammatory diseases - de Souza, Viviane Angelina (2025)
Background: The risk of tuberculosis infection (TBI) and its progression to tuberculosis disease (TBD) among persons with immune-mediated inflammatory diseases (IMID) results from a complex interplay of patient and disease characteristics, immunosuppression level, and the epidemiological context. Brazilian recommendations are unclear about TBI screening and its preventive treatment (TPT) in persons with IMID. Objective: To provide a comprehensive and evidence-based guideline for managing TBI in persons with IMID in Brazil. Methods: This task force was constituded by 42 specialists with interest in IMID and TBD. A core leadership team (CLT) drafted fourteen clinical questions on the risk of tuberculosis and indications of TPT among persons with IMID who started, or are about to start immunosuppressive drugs. The CLT supervised the systematic reviews and formulated the recommendations. The experts voted using the Delphi Method. Results: Nine recommendations were established. More than 80% of panelists voted “agree” and “strongly agree” with all statements. In brief, all persons with IMID starting or about to start immunosuppressive treatment should undergo tuberculin skin testing (TST) or interferon-gamma release assays (IGRAs), a chest imaging test and investigation of contact with active pulmonary or laryngeal TBD. TPT is mandatory for those with any positive result after excluding TBD. Exceptions include individuals with a history of TBD or a past positive TBI infection test. IGRA is preferred only in persons BCG-vaccinated in the past 2 years. Those with inconclusive IGRA results can have the test repeated once, and TPT should be offered if it remains indeterminate. TST or IGRA should be repeated yearly, for three years, when the previous test was negative, when starting or changing to a different class of immunosuppressive drug. Overall, the included studies had a low quality of evidence and high risk of bias. Conclusions: These guidelines are meant to improve the management of TBI in IMID. Health professionals must consider the epidemiological risk, host features, the social scenario, the characteristics of the disease, the access to health resources, and the development of an individualized plan for every patient.